Unveiling the Geometry of Culture: An Ethnomathematical Exploration of Transformation Geometry in Cimahi Batik Motifs - Purniati, Tia; Suhaedi, Didi (Jurnal Pendidikan MIPA, 2025)
Mathematics played an essential role in daily life. However, mathematics learning in schools was often less connected to students' real-life contexts, so many of them struggle to understand mathematical concepts. Relating mathematics to everyday life was necessary for students to understand its relevance and benefits. This research aimed to explore the cultural values and concepts of transformation geometry embedded in Cimahi batik motifs. The method used in this study was ethnographic, with the research conducted in Lembur Batik, Cimahi, West Java, Indonesia. The research framework in ethnomathematics adopted four key questions to inform the framework used to facilitate research, “Where should observations be made from?, "How is the observation process carried out?” "What are the results of these observations?", and “What is the meaning of it?. The investigator served as the instrument in the data-gathering process and used triangulation involving interviews, observations, and literature review. Analysis occurred in three stages: data condensation, data display, and drawing of conclusion. The study found that Cimahi batik motifs embody cultural values that reflect the identity of the Cimahi community. Moreover, these motifs employed concepts of transformation geometry, such as translation, reflection, rotation, and dilation. The distinctive feature of these findings is the association between the motif beauty of Cimahi batik and the use of transformation-geometry concepts derived from local culture. This is what makes the batik motif from Cimahi a valuable context for learning mathematics, particularly geometry. This has significant implications for the growth of ethnomathematics, as it means that geometrical concepts can be incorporated into local cultural frameworks within situational mathematics learning grounded in indigenous cultural knowledge.     Keywords: culture, transformation geometry, ethnomathematics, Cimahi batik motif.